Analisis Miskonsepsi dan Perbaikan Konsep Kesebangunan dan Kekongruenan pada Buku Matematika SMP dengan Metode Library Research (Studi Pustaka) - Windy.H; Rebecca.S; Nurul.N; Agung.B; Zuhra.M; Wingston Leonard Sihombing (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mathematics is an important part of education, from elementary school to college. Therefore, learning mathematics in elementary and middle school is very important for students, as it forms the basis for their academic development in the next level. One of the topics covered in the junior high school mathematics textbook is similarity and congruence, which are concepts related to the similarity of shapes and the comparison of sizes between two geometric figures. However, in practice, misconceptions are often found in the textbooks used. Misconceptions are understandings that are not in line with scientific definitions or do not correspond to the views agreed upon by mathematics experts. This study aims to: (1) identify misconceptions found in several junior high school mathematics textbooks on the material of similarity and congruence. (2) To identify corrections to misconceptions in mathematics textbooks by comparing the content of these textbooks with the correct definitions according to experts. (3) To identify corrections to these misconceptions by conducting proofs carried out by the author. The research method used is library research or literature study, which is carried out by identifying the research topic, formulating research questions, searching for literature, selecting literature, and finally analyzing the literature on junior high school mathematics textbooks on similarity and congruence. The results of the study revealed misconceptions about the meaning of congruence, leading to the correct and clear definition of congruence as two figures (geometric) that have the same shape, where corresponding angles are equal in size, and corresponding sides are equal or proportional in length, even though their sizes may differ.